Own, but not foreign seminal fluid inhibits sperm activation in a vertebrate with external fertilization - Rudolfsen, Geir; Vaz, Jonathan S.; Folstad, Ivar (Frontiers in Ecology and Evolution, 2015)
Seminal fluids are known to have a variety of effects on rival sperm, but in externally fertilizing species it is still unclear what effects seminal fluid can induce under sperm competition. We recorded sperm activity from natural ejaculates (including own seminal fluid) of an external fertilizer, the Arctic charr (Salvelinus alpinus), after activation either in water (the natural medium for milt dilution), in a dilution of water and own seminal fluid or in a dilution of water and seminal fluid of a foreign male. When activation occurred in own or foreign dilutions of seminal fluids, sperm maintained higher velocities than when activated in water only. Yet, velocity did not differ depending on whether sperm was activated in own or foreign seminal fluid solutions. More important, approximately 25% fewer sperm cells were initially activated in own seminal fluid than in foreign seminal fluid or water, indicating that activation is under close control of own seminal fluid only. Our results document that the presence of foreign seminal fluid under sperm competition do not have apparent effect on sperm velocity. Yet, the large inhibitory effect on initial activation of sperm cells seen in own, but not in foreign dilutions of seminal fluids (and water) suggests an individual specific recognition mechanism exerted by something in the seminal fluid on own, but not foreign sperm cells. The importance of this extrasomatic sperm recognition for the outcome of sperm competitions is discussed.